2002
DOI: 10.1021/np0103721
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Tumor-Promoting Effects by Poricoic Acids G and H and Other Lanostane-Type Triterpenes and Cytotoxic Activity of Poricoic Acids A and G from Poria cocos

Abstract: The structures of two novel 3,4-seco-lanostane-type triterpenes isolated from the sclerotium of Poria cocos were established to be 16alpha-hydroxy-3,4-seco-lanosta-4(28),8,24-triene-3,21-dioic acid (1; poricoic acid G) and 16alpha-hydroxy-3,4-seco-24-methyllanosta-4(28),8,24(24(1))-triene-3,21-dioic acid (2; poricoic acid H) on the basis of spectroscopic methods. These two, and eight other known compounds isolated from the sclerotium, poricoic acid B (3), poricoic acid A (4), tumulosic acid (5), dehydrotumulos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
92
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(95 citation statements)
references
References 20 publications
2
92
0
1
Order By: Relevance
“…Reversed-phase HPLC of the fractions enabled the isolation of poricoic acid A (compound 1) (5.0 mg), poricoic acid D (compound 2) (4.2 mg), poricoic acid G (compound 3) (3.3 mg) and poricoic acid H (compound 4) (2.8 mg) from fraction A, and tumulosic acid (compound 7) (2.5 mg), dehydrotumulosic acid (compound 8) (6.3 mg) and 3-epidehydrotumulosic acid (compound 9) (2.9 mg) from fraction B. 29) Isolation of dehydrotrametenonic acid (compound 5 ) and dehydroebriconic acid (compound 6) was undertaken as follows. Pulverized epidermis of the sclerotia (1 kg) was extracted with MeOH (3 liters) under reflux (3 h) three times.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reversed-phase HPLC of the fractions enabled the isolation of poricoic acid A (compound 1) (5.0 mg), poricoic acid D (compound 2) (4.2 mg), poricoic acid G (compound 3) (3.3 mg) and poricoic acid H (compound 4) (2.8 mg) from fraction A, and tumulosic acid (compound 7) (2.5 mg), dehydrotumulosic acid (compound 8) (6.3 mg) and 3-epidehydrotumulosic acid (compound 9) (2.9 mg) from fraction B. 29) Isolation of dehydrotrametenonic acid (compound 5 ) and dehydroebriconic acid (compound 6) was undertaken as follows. Pulverized epidermis of the sclerotia (1 kg) was extracted with MeOH (3 liters) under reflux (3 h) three times.…”
Section: Resultsmentioning
confidence: 99%
“…3,4) Whereas the inner parts, called Fu-Ling in Chinese, of the sclerotia of P. cocos were reported to have an invigorating activity in addition to diuretic and sedative activities, the epidermis (Fu-Ling-Pi in Chinese) of the sclerotia is reported to have only a diuretic activity and no invigorating activity. 3) Both the inner parts [4][5][6][7][8] and the epidermis 9,10) of the sclerotia of P. cocos were reported to contain several lanostane-type triterpene acids, 9,10) which were suggested to be the major medicinal components of the plant. Several of the lanostane-type triterpene acids were revealed to possess potent inhibitory effects on tumor cell growth.…”
mentioning
confidence: 99%
“…Previous studies have shown that PA could induce apoptosis in prostate cancer cells (Gapter et al, 2005). Lots of evidences have revealed that certain triterpenoids have anti-cancer activity, especially lanostane-type triterpenoids (Kaminaga et al, 1996;Ukiya et al, 2002). Another study has shown that PA could stimulate glucose uptake through enhance GLUT4 expression and translocation (Huang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…1) Whereas the inner parts, called Fu-Ling in Chinese, of the sclerotia of P. cocos are reported to have an invigorating activity in addition to diuretic and sedative activities, the epidermis (FuLing-Pi in Chinese) of the sclerotia is reported to have only a diuretic activity and no invigorating activity. 1) Various lanostane-type triterpene acids have been reported from the inner parts 2) and the epidermis 3) of the sclerotia of P. cocos. Several of these acids had potent inhibitory effects on 12-O-tetradecanoylphorbol-13-acetate (TPA)-induced inflammation in mice 4,5) and on Epstein-Barr virus early antigen (EBV-EA) activation induced by TPA, 2) as well as cytotoxicities against some human cancer cells.…”
mentioning
confidence: 99%